Influence of Bi Layer Structure and Sub Layer Distance on the Hardness of Multilayer Thin Film TiAlN and CrN / Siti Fatimah Hassan...[et al.] - Hassan, Siti Fatimah; Wan Zamri, Wan Fathul Hakim; Mohamed, Intan Fadhlina; Wan Ghopa, Wan Aizon; Md Din, Mohamad Faiz (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Mechanical properties are important in identifying the suitability of a material for a particular usage. One of the important properties is the hardness of the material, which can be defined as the resistance to the material to abrasion, deformation, scratching or to indentation by another hard body. Among others, this property is important for wear resistant applications. In order to obtain the mechanical characterization of thin films, apart from physical nanoindentation testing, researchers have also been using the finite-element modelling (FEM) method to simulate the nanoindentation test. In this study, a nanoindentation model of thin film CrN and TiAlN were developed and simulated to investigate the influence on the number of layers and thin film structure on the overall hardness of multilayer thin film CrN and TiAlN. A total of 10 sets of simulation was conducted with varying structural arrangement (i.e. CrN/TiAlN and TiAlN/CrN), bi-layer thickness (i.e. from 0.2 μm to 2 μm) and number of layers (i.e. 1, 2, 4, 8 and 10 layers). Based on the study, it was found that the optimum distance of sub base for multilayer TiAlN/CrN was 0.8 μm, while the optimum distance of sub-layer for CrN/TiAlN was 0 μm. It can be concluded that the type of material and the distance of sub base thin film layer to the maximum indenter depth will have significant influence on the overall hardness of the thin film system.